Assessment of Trace Metals in Water and Sediment in a Tropical River Potentially Affected by Land Use Activities in Northern Sarawak, Malaysia - Siong-Fong, Sim; Mugilan, Rajendran; Lee, Nyanti; Teck-Yee, Ling; Jongkar, Grinang; Jing-Jing, Liew (Springer, 2017)
This paper reports the trace metals in water and sediment of the Baram river in Northern Sarawak, Malaysia, a tropical river that is subjected to increasing land use activities, particularly logging. Water and sediment samples were collected from a total of 32 stations along the main and tributaries of the Baram river in triplicates. Water samples were digested based on the open acid digestion method whilst sediment was microwave digested. The samples were analysed with microwave plasma atomic emission spectrometer for arsenic (As), chromium (Cr), copper (Cu), iron (Fe), lead (Pb), manganese (Mn), nickel (Ni), selenium (Se) and zinc (Zn). Mercury (Hg) was analysed using the flow injection system. The background values of metals in water were determined based on 95th percentile of unaffected samples. For sediment, the baseline values were derived from the cumulative distribution curves with kneedle algorithm incorporated to improve the identification of background thresholds for assessment of contamination. The contamination factors suggest enrichment of Al, Fe, Mn, particularly at stations downstream where substantial development of oil palm plantations and land clearing activities were found. Significant correlations between Al, Fe and Mn in water suggest similar origin, possibly from surface runoff as these elements are prominently found in sediment. This study reveals that logging activities adjacent to the Baram river has caused accelerated surface runoff affecting the balance of Al, Fe and Mn in the environment.